Increased Incidence of Oral Cancer in Patients With Obstructive Sleep Apnea: Results From National Insurance Claims Data 2007–2014 - Eun Jung Lee; Jae Hoon Cho (Sleep Medicine Research, 2023)
Few studies have shown an increased risk of oral cancer in patients with obstructive sleep apnea syndrome (OSAS). We investigated the association between OSAS and oral cancer using data from the Korea National Health Insurance Service database. A total of 198574 male patients who were newly diagnosed with OSAS between 2007 and 2014 were included. A control group of 992870 participants was selected using propensity score matching, and the hazard ratio for oral cancer (95% confidence interval) was calculated. The incidence of oral cancer among patients with OSAS was significantly higher than that of the controls (1.25 [1.01–1.54]). Regarding oral cancer incidence by sex, there was no increase in the hazard ratio in males, but it increased to 2.29 (2.29 [1.38–3.70]) in females. In particular, the incidence of oral cancer was the highest in patients aged 40–65 years (1.38 [1.07–1.75]).